2015
DOI: 10.4040/jkan.2015.45.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Physical Activity among Community-dwelling Older Adults with Type 2 Diabetes: A Path Analysis

Abstract: Purpose: The purpose of the study was to identify factors influencing physical activity among community-dwelling older adults with type 2 diabetes. The study design was based on the Theory of Triadic Influence. Methods: A total of 242 older adults with type 2 diabetes participated in this study. Six variables related to physical activity in older adults, including self-efficacy, social normative belief, attitudes, intention, experience, and level of physical activity, were measured using reliable instruments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Additionally, only 6.7% of the participants were using insulin, signifying that most had relatively light symptoms. However, as recent studies of communitydwelling older Koreans with type 2 diabetes have reported that only 4-7.9% of them were using insulin (Jang, Park, Kim, & Chang, 2015;Kim et al, 2008), the insulin usage of this study's participants reflected that of this population.…”
Section: Limitations Of the Studycontrasting
confidence: 51%
“…Additionally, only 6.7% of the participants were using insulin, signifying that most had relatively light symptoms. However, as recent studies of communitydwelling older Koreans with type 2 diabetes have reported that only 4-7.9% of them were using insulin (Jang, Park, Kim, & Chang, 2015;Kim et al, 2008), the insulin usage of this study's participants reflected that of this population.…”
Section: Limitations Of the Studycontrasting
confidence: 51%
“…Moreover, the blood glucose levels in the control group were significantly higher than those in the experimental group after the intervention. In related studies [8,10,[17][18][19][20], older adults that participated in a physical activity program showed physical function improvement, compared with older adults that did not participate.…”
Section: Discussionmentioning
confidence: 98%
“…The TTI is characterized by the fact that each stream independently influences behavioral intention and behavior. Its benefit is its consideration of cultural aspects in understanding the behaviors of individuals …”
Section: Introductionmentioning
confidence: 99%